2009
DOI: 10.1542/peds.2008-1508
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Bonded Central Venous Catheters Do Not Reduce Thrombosis in Infants With Congenital Heart Disease: A Blinded Randomized, Controlled Trial

Abstract: Infants with congenital heart disease are at significant risk of both silent and clinically identified thrombosis. There seems to be no advantage in using heparin-bonded catheters in infants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 14 publications
1
52
0
Order By: Relevance
“…In a recent pediatric randomized, controlled, blinded, single-center trial, infants younger than 1 year old with congenital heart disease requiring a central venous line for clinical care were randomly assigned to receive either a heparin-bonded catheter or a standard non-heparin-bonded catheter. No advantage in using heparin-bonded catheters was identified [82]. All things considered, the data remain insufficient to recommend the systematic use of either of these catheters.…”
Section: Prevention Of Bsismentioning
confidence: 99%
“…In a recent pediatric randomized, controlled, blinded, single-center trial, infants younger than 1 year old with congenital heart disease requiring a central venous line for clinical care were randomly assigned to receive either a heparin-bonded catheter or a standard non-heparin-bonded catheter. No advantage in using heparin-bonded catheters was identified [82]. All things considered, the data remain insufficient to recommend the systematic use of either of these catheters.…”
Section: Prevention Of Bsismentioning
confidence: 99%
“…Systemic anticoagulation, however, places patients at high risk for bleeding, which often can be life-threatening. Although extensive work has been done to develop extracorporeal circuits with nonthrombogenic surface properties, clinical success has been equivocal and the use of such devices has been limited to specific clinical scenarios 18 . The ideal biomaterial for extracorporeal circulatory devices is one that is similar to vascular endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombi usually develop within several days after the catheter has been inserted. Prospective studies have revealed that deep vein thrombosis develops in 12−28% of the children [35,36]; in infants, this risk is higher, i.e., 44% [37]. Therefore, thrombosis in children with central venous catheters has been increasingly considered to be a significant problem, especially because none of the methods used has been demonstrated to provide full protection, except for the removal of cannulas as soon as possible.…”
Section: Intravenous Accessesmentioning
confidence: 99%